CTnDOT integrase performs ordered homology-dependent and homology-independent strand exchanges - Malanowska, Karolina (Oxford University Press, 2007)
Although the integrase (IntDOT) of the Bacteroides conjugative transposon CTnDOT has been classified as a member of the tyrosine recombinase family, the reaction it catalyzes appears to differ in some features from reactions catalyzed by other tyrosine recombinases. We tested the ability of IntDOT to cleave and ligate activated attDOT substrates in the presence of mismatches. Unlike other tyrosine recombinases, the results revealed that IntDOT is able to perform ligation reactions even when all the bases within the crossover region are mispaired. We also show that there is a strong bias in the order of strand exchanges during integrative recombination. The top strands are exchanged first in reactions that appear to require 2 bp of homology between the partner sites adjacent to the sites of cleavage. The bottom strands are exchanged next in reactions that do not require homology between the partner sites. This mode of coordination of strand exchanges is unique among tyrosine recombinases.